The golden sandal : a Middle Eastern Cinderella story - Hickox, Rebecca (Holiday House, 1998)
An Iraqi version of the Cinderella story in which a kind and beautiful girl who is mistreated by her stepmother and stepsister finds a husband with the help of a magic fish.